2021
DOI: 10.33323/indigenous.v4i2.151
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Tumbuhan Dalam Proses Pewarnaan Kain Tenun Ikat Di Pulau Ndao, Desa Ndao Nuse, Kabupaten Rote Ndao

Abstract: ABSTRACT This study aims to determine the types of natural coloring plants, organs plant or parts used, the processing to the colors produced from plants organs used in the process of coloring woven cloth on Ndao Island, Ndao Nuse Village, Ndao Nuse  sub-district, Rote Ndao Regency. The method used is a qualitative descriptive method. The technique used in this study is direct observation techniques in the field and semi-structured interviews. Semi-structured interviews are interview processes that use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of interviews with respondents indicate that the community is more familiar with Indigofera for use to produce black dye rather than blue, a finding supported by two other studies (Ledoh et al 2021;Nomleni et al 2019). The black color is obtained by mixing clay with Indigofera spp.…”
Section: Evaluation Of the Cultivation And Utilization Of Indigofera Sppsupporting
confidence: 55%
See 1 more Smart Citation
“…The results of interviews with respondents indicate that the community is more familiar with Indigofera for use to produce black dye rather than blue, a finding supported by two other studies (Ledoh et al 2021;Nomleni et al 2019). The black color is obtained by mixing clay with Indigofera spp.…”
Section: Evaluation Of the Cultivation And Utilization Of Indigofera Sppsupporting
confidence: 55%
“…Ikat reflects the identity of the different ethnic groups in NTT, with each group having a different style (Susilawati 2010), such as representations of animals (Sumba Island), leaves (Rote Island), silk and embroidery weaving (Timor Island), and warp ikat weaving (Alor Islands) (Salma et al 2018;Sulayman et al 2017), also colors that differ widely from those found elsewhere in the archipelago (Dioh 2020) due to the use of natural dyes in its production (Ledoh et al 2021;Murniati and Takandjandji 2015;Nomleni et al 2019;Sabuna and Nomleni 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tahap ekstraksi inilah yang membedakan cara pengolahannya. Ledoh et al (2021) menyatakan bahwa tujuan tahapan ekstraksi adalah agar cairan yang terdapat di dalam organ tumbuhan tersebut keluar dan diserap oleh benang. Pada cara pengolahan yang tidak direbus, bagian tumbuhan ditumbuk dan langsung dicampur dengan benang.…”
Section: Cara Pengolahan Tumbuhan Menjadi Pewarna Benangunclassified
“…Beberapa penelitian menyebutkan ada beberapa jenis tanaman yang digunakan untuk pewarna seperti kulit batang mahoni (Swietenia mahagoni), daun turi (Sesbania grandiflora), dan rimpang kunyit (Curcuma domestica) untuk mewarnai benang tenun ikat dari Desa Harona Kalla, Laboya, Sumba. Sedangkan bahan alami untuk pengikat warna seperti akar biduri, kulit batang kedondong pagar, kapur sirih, karat besi sebagai pengikat warna dan cuka sebagai pengawet warna pada benang [14] Potensi Tenun Ikat Sebagai Sumber Belajar 112 nigritana) menghasilkan warna cokelat, jarak merah (Jatropha gossiphofolia) untuk warna hijau [19]. Selain pada bidang IPA/sains motif kain pada tenun juga dihubungkan dengan penerapan konsep sudut dan titik sudut pada bidang matematika seperti yang dilaporkan oleh penelitian sebelumnya serta konsep dilatasi pada motif mamuli dan papiarang, serta konsep pencerminan benda pada sumbu x dan y seperti perputaran motif (rotasi 180 0 ) atau pencerminan translasi pada motif tertentu [7].…”
Section: Hasil Dan Diskusiunclassified